Management of Upper Gastrointestinal Bleeding due to NSAID Gastropathy that is Unresponsive to Ranitidine - Lusy Erawati; Sayid Ridho; Ginova Nainggolan; Ari Fahrial Syam; Chudahman Manan (The Indonesian Society for Digestive Endoscopy, 2003)
Non steroidal anti-inflammatory drugs (NSAIDS) are now commonly used in clinical practice. On the other hands, this drug could result severe complication such as bleeding and perforation. In such condition, proton pump inhibitor can be used to stop bleeding than H2 antagonists. We reported one cases of upper gastrointestinal bleeding due to NSAID gastropathy that was unresponsive to Ranitidine. The treatment was suitable to proton pump inhibitor that could overcome upper gastrointestinal bleeding.